Localization-Specific Expression of CCR1 and CCR5 by Mast Cell Progenitors - Salomonsson, Maya; Dahlin, Joakim S.; Ungerstedt, Johanna; Hallgren, Jenny (Frontiers in Immunology, 2020)
Mast cells are powerful immune cells found predominately in barrier tissues. They play an important role in immune surveillance and act as effector cells in allergic reactions. Mast cells develop from mast cell progenitors (MCp), which migrate to the peripheral tissues via the blood circulation. Presumably, the homing of MCp to the peripheral sites and localization is regulated by chemotactic signals. Due to the scarce abundance of these cells, chemotactic receptors have not been previously characterized on primary MCp. Here, mRNA transcripts for CCR1 and CX3CR1 were identified in mouse bone marrow and lung MCp in a gene expression screen of chemotactic receptors. However, surface expression of CCR1 was only found in the bone marrow MCp. Flow cytometry-based screening identified distinct surface expression of CCR5 by mouse peritoneal mast cells and MCp, while surface expression of CXCR2-5, CX3CR1, CCR1-3, CCR6-7 and CCR9 was not detected. Low surface expression of CCR5 was detected in mouse MCp in the bone marrow, spleen and lung. To translate the findings to human, blood and bone marrow MCp from healthy donors were analyzed for possible CCR1 and CCR5 expression. Human MCp showed distinct surface expression of both CCR1 and CCR5. The expression levels of these chemokine receptors were higher in human bone marrow MCp than in the peripheral blood, suggesting that CCR1 and CCR5 may mediate retention in the bone marrow. In conclusion, mouse and human MCp show differential expression of CCR1 and CCR5 depending on their localization.